Assessment of Socio-Digital Approaches for Agricultural Extension in Shri Muktsar Sahib District of Punjab (Indian Journal of Extension Education, 2020)
Electronic and print media has always played an important in transfer of technology. Now the social media has been becoming instrumental in bringing changes in behavior of people. Keeping in view the importance of social media, the Krishi Vigyan Kendra, Sri Muktsar Sahib started using social media for the purpose of agricultural extension. This centre has enrolled 799 farmers for spreading scientific technologies among farmers. To study the preference and constraints faced by farmers in using social media, a survey of 250 respondents was conducted during the year 2019. The majority (56.4%) of the respondents selected in the study were in the middle age group, medium level education and medium land holdings of size. The results revealed that social media has become a preferred source of information for farmers. Only 0.8 per cent of the farmers preferred radio as source of information, 7.2 per cent preferred television, while 70 per cent of the farmers preferred social media (WhatsApp) as source of information for latest agricultural technology. The preference for use of social media in agricultural extension had significant correlation with age, education, media exposure, economic motivation and socio-economic status. Fake and irrelevant messages were considered as major problem in communication through social media by majority of the farmers. Present study indicates the increasing importance of social media for transfer of technology to farmers.